Bioethics after Posthumanism: Natural Law, Communicative Action and the Problem of Self-Design - Graham, Elaine L. (Journal for the study of religion, nature and culture, 2004)
Three recent books by prominent social and political theorists (Francis Fukuyama, Gregory Stock and Jürgen Habermas) have engaged with the impact of biotechnology on our very concepts of human nature, and the corresponding challenges to ethical discourse of the so-called ‘posthuman condition’. All three writers raise important questions about the role of concepts of ‘human nature’ in moral discourse, and the paper will subject their claims to theological critique. I conclude by proposing, after Peter Scott (2003), that to consider humanity as ‘un/natural’ serves to affirm human interdependence with, rather than transcendence or dominion over, nature; but that similarly, talk of nature itself as ‘post/human’ restores to it a divinely-conferred integrity, liberated from the self-serving interests of technoscientific objectification.